A variant version of Hikayat Iblis - Raimy Ché-Ross (Universiti Kebangsaan Malaysia, 2002)
Relatively unknown even in learned circles, Hikayat Iblis has long been regarded as an obscure and inconsequential text in Malay-Islamic literary studies. Having fallen into the ignominy of misinterpretations and superficial readings, existing evaluations of the text are dismissive at best. The following essay seeks to reconsider the work in a more positive light, by highlighting the hitherto neglected inherent nature of the tale. A variant version of the work will also be presented and discussed for the first time. By doing so, it is hoped that it will encourage us to reassess Hikayat Iblis as a significant and important example of its corpus and genre